2019
DOI: 10.1177/2150132719874252
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Accelerometers for Measuring Physical Activity and Levels of Sedentary Behavior in Children: A Systematic Review

Abstract: Objectives: This systematic review evaluated the accuracy of triaxial and omnidirectional accelerometers for measuring physical activity and sedentary behavior in children. Design: Systematic review of the literature. Methods: We comprehensively searched several databases for studies published from January 1996 through June 2018 that reported diagnostic accuracy measures in children and adolescents (age 3-18 years) and compared accelerometers with energy expenditure using indirect calorimetry. Results: We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…However, experimental researches show that even the more advanced technology of the IDEA underestimated the burning of calories when walking slowly, but overestimated the speed of walking [20]. Despite the research data, many mobile algorithms have not been confirmed by experimental researches [1,15]. An overabundance of proposed mobile applications and guidelines saturates the fitness market with lowquality information and algorithms [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental researches show that even the more advanced technology of the IDEA underestimated the burning of calories when walking slowly, but overestimated the speed of walking [20]. Despite the research data, many mobile algorithms have not been confirmed by experimental researches [1,15]. An overabundance of proposed mobile applications and guidelines saturates the fitness market with lowquality information and algorithms [21].…”
Section: Resultsmentioning
confidence: 99%
“…It is the systematic, stable, and uniform performance of the aerobic motor activity in training sessions and in General in daily and weekly modes that ensures the transition of the body urgent adaptive responses to loads long-term adaptation [12][13][14]. Violation of the regularity principle and uniformity in the course of training may not only give the desired health-improving effect, but also leads to serious health disorders [15,16]. Only a strictly individual-differentiated approach to the implementation of aerobic physical activity on the basis of systematic self-analysis of energy exchange through the account of consumed and allocated body calories will ensure physical and health success [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies use only the accelerometer as a device for assessing sedentary behavior, 14,16 and there are some limitations in the interpretation of these data. Despite presenting acceptable reliability and validity for physical activity in pediatric populations, 40,41 accelerometers overestimate sedentary behavior among school time and longitudinal data when compared to inclinometers because of the limitation of detecting postures. 42 On the other hand, inclinometers enabled more accurate identification of total sitting time in the school context, 19 but they have not been well validated for assessment of various intensities of physical activity in children.…”
Section: Discussionmentioning
confidence: 99%
“…38 Activity monitors and accelerometry also have limited accuracy that changes based upon several factors including the device itself and where it is worn. 39 Further research is needed to both quantify and qualify the amount and type of physical activity among American children schooled at home.…”
Section: Discussionmentioning
confidence: 99%